Towards an Inclusive Pedagogy: Applying the Universal Design for Learning in an Introduction to History of Global Art Course in Ghana - Adom, Dickson; Abroampa, Winston Kwame; Amoako, Richard; Toquero, Cathy Mae; Kquofi, Steve (Journal of Contemporary Issues in Education, 2023)
This convergent parallel mixed methods study was aimed at addressing the lack of empirical studies in the implementation of Universal Design for Learning (UDL) as an inclusive pedagogy in the Ghanaian higher education context. The overarching objective was to find out whether UDL has the potential in improving the learning processes and learning outcomes of the diverse students reading a History of Global Art course. Quantitative and qualitative data sets were garnered from 122 conveniently sampled students using an adapted version of the Inclusive Teaching Strategies Inventory-Students (ITSI-S) survey instrument. The findings of the study revealed that the UDL principles of multiple means of representation, multiple means of engagement and multiple means of action and expression impacted positively on students’ learning processes and outcomes. UDL assisted greatly in the development of collaborative, problem-solving, good time management and critical thinking skills, while increasing learners’ level of motivation. The study contends that though the UDL as an inclusive pedagogical approach requires a lot of dedication on the part of the instructor as well as a great deal of time and material resources, the accrued benefits of its implementation on the students’ learning processes and learning outcomes are far-reaching.